Assessing the Role of Local Government Towards the Development of Tourism in Rwanda: A Case Study of Musanze District. - Tuyishime, Jean Claude (Kabale University, 2023)
The exploitation of natural resources has been attributed to the fact that the human population keeps enlarging, thus there is a lot of pressure on the utilization of natural resources. Other challenges like poaching. deforestation, grazing, and bush burning lead to the destruction of tourism destinations and the environment at large thus impacting the eco-systems within the environment and causing environmental erosion. The study examined the contribution of Local development of tourism destinations in Rwanda in Musanze District.